2014
DOI: 10.1093/cercor/bhu046
|View full text |Cite
|
Sign up to set email alerts
|

Neural Correlates of Spatial Attention and Target Detection in a Multi-Target Environment

Abstract: Our ability to attend and respond in a multi-target environment is an essential and distinct human skill, as is dramatically demonstrated in stroke patients suffering from extinction. We performed a functional magnetic resonance imaging study to determine the neural anatomy associated with attending and responding to simultaneously presented targets. In healthy subjects, we tested the hypothesis that the right intraparietal sulcus (IPS) is associated both with the top-down direction of attention to multiple ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 55 publications
7
28
0
Order By: Relevance
“…Furthermore, it offers a framework within which specific hypotheses can be tested concerning the relationship between rightward PA and different aspects of attention. First, the bilateral visual representation, which is uncovered by rightward PA within the left IPL, may be the same as recruited in paradigms of high attentional load (de Haan et al, 2015) or it may be related to the motor attentional system (Rushworth et al, 2003(Rushworth et al, , 2001. Second, seminal studies have revealed fine-tuned interactions between the ventral and the dorsal systems and their breakdown following damage to the ventral system (Corbetta and Shulman, 2011;Koch et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it offers a framework within which specific hypotheses can be tested concerning the relationship between rightward PA and different aspects of attention. First, the bilateral visual representation, which is uncovered by rightward PA within the left IPL, may be the same as recruited in paradigms of high attentional load (de Haan et al, 2015) or it may be related to the motor attentional system (Rushworth et al, 2003(Rushworth et al, , 2001. Second, seminal studies have revealed fine-tuned interactions between the ventral and the dorsal systems and their breakdown following damage to the ventral system (Corbetta and Shulman, 2011;Koch et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a recent study of target detection in multi-target environments hints at such a possibility. When analyzing neural responses within regions with a preference for uncued over cued targets, de Haan and colleagues (de Haan et al, 2015) reported equal levels of activity for ipsilateral and contralateral (unilateral) targets within a large right TPJ region and within a small left TPJ cluster. It is likely that the bilateral visual representation within the left TPJ, which went unreported in a series of previous studies, was revealed here due to the high attentional load of the complex paradigm.…”
Section: Effects Of Rightward Prismatic Adaptation In Normal Subjectsmentioning
confidence: 99%
“…The choice for this task was motivated by two sets of observations from the previous literature: Firstly, previous studies have demonstrated that comparing neural activation during bilateral object identification trials and neural activation during unilateral object identification trials enables isolating the right IPS area associated with attention in multi-target environments (Çiçek et al, 2007;de Haan, Bither, et al, 2015;Geng et al, 2006). The choice for this task was motivated by two sets of observations from the previous literature: Firstly, previous studies have demonstrated that comparing neural activation during bilateral object identification trials and neural activation during unilateral object identification trials enables isolating the right IPS area associated with attention in multi-target environments (Çiçek et al, 2007;de Haan, Bither, et al, 2015;Geng et al, 2006).…”
Section: Session 1: Fmri Localizermentioning
confidence: 99%
“…This lateralized spatio-attentional deficit in extinction patients may be exacerbated by nonlateralized deficits of selective attention, such as a reduction of attentional capacity, so that ultimately only the ipsilesional target is attentionally selected and available for overt report (de Haan et al, 2012;Driver, Mattingley, Rorden, & Davis, 1997;Karnath, 1988). In neurologically healthy subjects, the right (de Haan, Bither, et al, 2015), or right and left (Çiçek, Gitelman, Hurley, Nobre, & Mesulam, 2007;Geng et al, 2006) IPS show(s) higher levels of neural activation when attention is bilaterally oriented compared to situations where the focus of attention is unilateral. Two brain regions are thought to be involved in our ability to attend to multiple simultaneously-presented lateralized targets, and the failure of this ability in extinction patients.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, attentional response to the stop/no-go signal may explain greater IFC activation during stop (or no-go) trials compared with go trials (Aron & Poldrack, 2006;Chevrier et al, 2007;Congdon et al, 2010;Garavan et al, 1999;Konishi et al, 1999;Leung & Cai, 2007;Liddle et al, 2001;Rubia et al, 2003). Many other studies likewise support a role of the IFC in target detection, even when response inhibition is not engaged or specifically discouraged (Bledowski et al, 2004;de Haan et al, 2014;Hampshire et al, 2009;Linden et al, 1999;Nardo et al, 2011;Weissman & Prado, 2012). For instance, the IFC responds to target stimuli even when they are equated in frequency to the distractor stimuli or when response suppression is not required (Hampshire et al, 2009) and to stimuli that are previously associated with stop but currently instructs a response (Lenartowicz et al, 2011).…”
Section: Imaging Studies Of the Ifcmentioning
confidence: 96%